2015
DOI: 10.1128/jcm.03040-14
|View full text |Cite
|
Sign up to set email alerts
|

Ruminococcus gnavus Total Hip Arthroplasty Infection in a 62-Year-Old Man with Ulcerative Colitis

Abstract: We report the case of a total hip arthroplasty infection caused by Ruminococcus gnavus in a 62-year-old man with ulcerative colitis. The bacterium was perfectly identified by matrix-assisted laser desorption ionization-time of flight mass spectrometry. CASE REPORTA 62-year-old man was referred to the orthopedic surgery department of a suburban clinic with suspected prosthetic joint infection (PJI) of the right hip. This patient had undergone total right hip replacement 13 years earlier and had shown no signs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 16 publications
2
16
0
Order By: Relevance
“…In addition to its increased abundance in IBD, other studies have implicated R. gnavus as a potential pathobiont. Three cases of R. gnavus bacteremia and a case of infection of the bone surrounding a hip implant by R. gnavus have been reported [ 28 30 ]. In a study about treating UC patients with fecal microbiome transplants, patients who received stool from donors with high R. gnavus were more likely to relapse [ 31 ], suggesting a causal role in disease.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its increased abundance in IBD, other studies have implicated R. gnavus as a potential pathobiont. Three cases of R. gnavus bacteremia and a case of infection of the bone surrounding a hip implant by R. gnavus have been reported [ 28 30 ]. In a study about treating UC patients with fecal microbiome transplants, patients who received stool from donors with high R. gnavus were more likely to relapse [ 31 ], suggesting a causal role in disease.…”
Section: Discussionmentioning
confidence: 99%
“…Butyrate-producing bacteria are promising probiotic candidates targeting microbiota modulation in gastrointestinal disorders such as IBD [ 16 ]. Similarly, Ruminococcus gnavus , a member of the Ruminococcaceae family, has been reported to be implicated in infection following artificial hip joint replacement [ 17 ], liver abscess due to Ruminococcus gnavus , and infective endocarditis. In addition, reports have shown that Ruminococcus is involved in the development of cerebral and myocardial infarction [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ruminococcus gnavus is a strict anaerobic Gram-positive coccus, which has been described as being part of the normal intestinal flora in humans [1]. To date, only nine cases of R. gnavus infections have been reported in the literature, predominantly in patients with gastrointestinal symptoms or prosthesis infection [2][3][4][5][6][7][8][9]. We present the first case of R. gnavus bacteraemia in a patient with multiple haematological malignancies, and with no abdominal complaint or prosthesis infection.…”
Section: Introductionmentioning
confidence: 99%
“…Of the nine cases found, six involved patients with a background of gastrointestinal (GI) diseases such as diverticular disease, ulcerative colitis and cholecystitis [2][3][4][5][6], and one more was hypothesized to have had a GI fistula [7]. In four of the cases, the bacteria were found in a hip (native or alloplastic) [4,[7][8][9]. See Table 1 for further information on previous cases.…”
Section: Introductionmentioning
confidence: 99%